Discards survival probability estimates (%) and their 95% confidence intervals, direct mortality and survival of control fish for spotted and thornback skate discarded by beam trawl, pulse trawl, and flyshoot fisheries. - Edward Schram (405230) (2024)
Survival probability estimates within species and per gear with different letters in superscript are significantly different. Note that no comparisons between species were made.